2021
DOI: 10.3390/antibiotics10080926
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Baicalin against Clostridioides difficile Infection in Mice

Abstract: This study investigated the prophylactic and therapeutic efficacies of baicalin (BC), a plant-derived flavone glycoside, in reducing the severity of Clostridioides difficile infection (CDI) in a mouse model. In the prophylactic trial, C57BL/6 mice were provided with BC (0, 11, and 22 mg/L in drinking water) from 12 days before C. difficile challenge through the end of the experiment, whereas BC administration started day 1 post challenge in the therapeutic trial. Both challenge and control groups were infected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 62 publications
(75 reference statements)
0
3
0
Order By: Relevance
“…Some studies show that CDI patients and mouse model have a low abundance of A. muciniphila ( Rodriguez et al, 2016 ; Deng et al, 2018 ; Pellissery et al, 2021 ), while an increased number of A. muciniphila was observed in other studies ( Sangster et al, 2016 ; Vakili et al, 2020 ; Shoaei et al, 2021 ). This contradictory conclusion associates to various factors.…”
Section: Discussionmentioning
confidence: 93%
“…Some studies show that CDI patients and mouse model have a low abundance of A. muciniphila ( Rodriguez et al, 2016 ; Deng et al, 2018 ; Pellissery et al, 2021 ), while an increased number of A. muciniphila was observed in other studies ( Sangster et al, 2016 ; Vakili et al, 2020 ; Shoaei et al, 2021 ). This contradictory conclusion associates to various factors.…”
Section: Discussionmentioning
confidence: 93%
“…This Special Issue also includes the trial by Pellissery et al to investigate the prophylactic and therapeutic efficacies of baicalin, a plant-derived flavone glycoside, in reducing the severity of CDI [18]. In the prophylactic trial, mice were provided with baicalin from 12 days before CD challenge through the end of the experiment, whereas baicalin administration started on day 1 post-challenge in the therapeutic trial.…”
mentioning
confidence: 99%
“…The authors reported that both prophylactic and therapeutic supplementation of baicalin significantly reduced the severity of colonic lesions and improved CDI clinical progression and outcome compared with the control. Moreover, the authors highlighted that baicalin supplementation favorably altered the mice microbiome composition [18].…”
mentioning
confidence: 99%